Design of Smoke Detector for Smart Room Based on Arduino Uno - Dirja Nur Ilham; Rudi Arif Candra; Muhammed Saat Talib; Mario di Nardo; Khusnul Azima (ITScience (Information Technology and Science), 2021)
Smoke is one of the air pollutions that is very detrimental to the health of both the smoker himself and others around him. Inhaling other people's smoke is even more dangerous than inhaling your own smoke. Even the dangers that must be borne by passive smokers are three times greater than the dangers of active smokers. Smoke is also very detrimental to the health of patients in hospitals, especially patients who suffer from asthma. For people with asthma who have problems in the respiratory tract, asthma can recur at any time due to inhaling smoke. This research will develop a smart room that can detect smoke to maintain and protect the room from smoke that interferes with health. The tool to be developed uses an MQ2 sensor, LCD, exhaust fan, buzzer, and Arduino Uno microcontroller. Where an MQ2 sensor is needed to detect smoke around it, an LCD is needed to display the percentage of smoke, a microcontroller as a controller for all components, a buzzer is used as an alarm when the smoke level in the room is unhealthy, and the exhaust fan functions as a sucker for dirty air so that the smoke level in the room can be reduced.